KECERNAAN IN-VITRO, VOLLATYLE FATTY ACID, DAN AMONIA SILASE JERAMI JAGUNG DENGAN LAMA WAKTU PENYIMPANAN BERBEDA - A.A.A.S. Trisnadewi; I G.L. Oka Cakra; T.G.B. Yadnya (Udayana University, 2018)
The study aimed to determine invitro digestibility, volattyle fatty acid (VFA) and ammonia (NH3) of corn straw silage with different storage periode. The experiments use a completely randomized design (CRD) with four treatments and each treatment was repeated five times, so there are 20 experimental units. The fourth treatments are W1 = storage time of 14 days, W2 = storage time of 21 days, W3 = storage time of 28 days, and W4 = storage time of 35 days. The parameters observed in this study in-vitro digestibility including dry matter and organic matter digestibility, VFA, and NH3. Results of the experiment showed that dry matter digestibility showed significant differences, otherwise organic matter digestibility, VFA, and NH3 were not significantly different, and there was a tendency to decrease the value of dry matter and organic matter digestibility, VFA, and NH3 with longer duration of storage of corn straw silage. It can be concluded that dry matter, organic matter digestibility VFA, and NH3, are not significant different. Keywords: corn straw, silage, storage periode, invitro digestibility, VFA, NH3